WETLANDS VIEWPOINT BASED ON ENGLISH EDUCATION DEPARTMENT STUDENTS AT LAMBUNG MANGKURAT UNIVERSITY - Asmi Rusmanayanti (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2020)
Vocabulary mastery, especially related to wetlands also need to be considered deeply because it is a common area in Kalimantan. English Language Educational Department at ULM is on part of the Faculty of Teacher Training and Education which deals with many schools and students who live in a wetland area. Therefore, the knowledge about the surrounding areas and try to integrate the local knowledge or culture is necessary. This research is focusing on the English Language Educational Department Students’ view with regard to their environment. It is expected if they know more about their surroundings, they can be more creative in integrating their knowledge in English and modified the material that is familiar to their future students. It is a qualitative research with 25 English Language Educational Department Students as the sample. The instruments are questionnaires, interviews, and documentation. The result of this research shows that the students of the English Language Educational Department mentioned that it is necessary to add more vocabulary and reading texts or journals related to wetlands in the Department. They also mention write some common vocabularies relate to wetlands.